A comparative experimental study on the performance of mixing ventilation and stratum ventilation for space heating. (15th June 2019) - Kong, Xiangfei; Xi, Chang; Li, Han; Lin, Zhang
Abstract: In this paper, a comparative experimental study on the performance of mixing ventilation and stratum ventilation for space heating was carried out. Objective and subjective experiments were both conducted to explore the difference of the thermal performance between the two types of ventilation. In the objective experiment, air temperature distribution, air velocity distribution, and ventilation effectiveness of stratum ventilation and mixing ventilation were discussed. Research results found that stratum ventilation can realize to reduce energy consumption by 25% compared with mixing ventilation. Meanwhile, the indoor thermal comfort was also investigated in this study. Overall thermal sensation and comfort (OTS and OTC), effective draft temperature (EDT) and vertical air temperature difference (VTD) were introduced as the evaluation indicators. By employing stratum ventilation for heating, the indoor comfort can be enhanced by 10.0% with the same supply air parameters as mixing ventilation. As a whole, stratum ventilation showed excellent performance not only on energy saving but also the indoor comfort for space heating. The data obtained in this study can also provide a reference for the design and optimization of stratum ventilation used for space heating. Highlights: An experimental study on mixing ventilation and stratum ventilation was conducted. Objective and subjective experiments were both carried out in this study. Stratum ventilation can save 25% energy relative to mixing ventilation. Stratum ventilation can also enhance the indoor comfort by 10.0%. Our findings provide guidelines for using stratum ventilation in clean heating.